Relationship between the prevalence of cardiometabolic diseases and the presence of psoriatic arthritis in Russian patients with psoriasis - E. V. Bogdanova; A. A. Kubanov (Современная ревматология, 2023)
Psoriasis is associated with an increased risk of cardiometabolic pathology. Comparative studies of this pathology’s prevalence in patients with psoriasis depending on the presence of psoriatic arthritis (PsA) in a representative sample of Russian patients have not been conducted.Objective:to compare the prevalence of cardiometabolic diseases in Russian patients with psoriasis depending on the presence or absence of PsA.Material and methods. The data of the register of patients with psoriasis of the Russian Society of dermatovenerologists and Cosmetologists (RODVK) were analyzed. Inclusion criteria: age >18 years, information about the established diagnosis of PsA. A comparison was made between patients with PsA and two comparison groups: all patients without PsA and patients without PsA with a duration of psoriasis exceeding the established value.Results and discussion. The analysis included 920 patients with PsA (group 1) and 2325 patients with psoriasis without PsA (group 2). Group 3 included 655 patients from group 2.The prevalence of cardiometabolic diseases in patients with PsA was higher than in group 2. When compared to group 3, the statistically significant differences were noted only for impaired glucose tolerance. However, adjusted for gender and age, patients with PsA had statistically significant higher chances of developing arterial hypertension (AH), coronary heart disease, angina pectoris, acute cerebrovascular accident, impaired glucose tolerance and diabetes mellitus than patients in group 3. When adjusting for disease risk factors, the statistical significance of differences remained for hypertension and angina pectoris.Conclusion. The prevalence of cardiometabolic diseases in Russian patients with PsA is higher than in patients with psoriasis without PsA.